పద్య మంజరి - (:unkn) unknown (Andhra Saraswata Parishath, 1962)
It's all about collection of poetry taken from various books
Padhya Manjari
Keywords: Telugu; పద్య మంజరి; Padhya Manjari; Literature; Telugu; Telugu